Gender and the science of difference : cultural politics of contemporary science and medicine - Fisher, Jill A., 1976- (Studies in modern science, technology, and the environment., 2011)
Gender and the Science of Difference examines how contemporary science shapes and is shaped by gender ideals and images. This interdisciplinary volume presents empirical inquiries into today's science, including examples of gendered scientific inquiry and medical interventions and research. It analyzes how scientific and medical knowledge produces gender norms through an emphasis on sex differences, and includes both U.S. and non-U.S. cases and examples.